Application of Project Management Information Systems in Efficiency Improvement of Quality Management System (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Project management information systems (PMIS) and quality management system (QMS) are two components in the project oriented organization that helps to achieve required quality of the project product. QMS define quality framework and PMIS helps to ensure quality framework requirement related to the projects. The objective of paper is to evaluate and demonstrate PMIS options for efficiency QMS development and maintenance. QMS requirements are identified according to ISO 9001:2008 standard and PMIS options of efficiency improvement are evaluated according to ISO 9004:2009 self-assessment tool.